Study on laser ablation characteristics of tree obstacles in transmission lines - Xu, Wenrong; Zhao, Yanhua; Chen, Wenjie; Fang, Chunhua; Hu, Tao; Huang, Bingyu; Zhang, Jin (Frontiers in Physics, 2024)
IntroductionAs a new and efficient method for obstacle removal, laser clearance has promising applications in eliminating tree obstacles in transmission lines. This paper aims to explore various aspects related to the laser ablation of tree obstacles in transmission lines through simulation and experimentation.MethodsThis paper employs simulation and experimentation to test the ignition time, burn-through time, peak temperature, and basic carbonization rate of various types of tree obstacles in transmission lines. Additionally, it analyzes the effects of tree density, laser power, clearance distance, and tree moisture content on laser ablation characteristics.ResultsThe results reveal that different types of tree obstacles exhibit distinct ablation characteristics. With increasing tree density, both the ignition and burn-through times increase, while the peak temperature and basic carbonization rate decrease. Additionally, laser power and clearance distance significantly influence laser ablation behavior. Higher laser energy density results in greater heat flux density, leading to shorter ignition and burn-through times and higher peak temperatures and carbonization rates. Moreover, the tree obstacle with the highest moisture content (58.4%) had the shortest burn-through time of 46.56 s, whereas the one with the lowest moisture content (14.8%) took the longest at 58.41 s, which demonstrates that increased moisture content enhances the laser ablation rate.DiscussionThese findings provide a basis for the application of laser-based tree obstacle removal in power transmission lines. The understanding of how different factors such as tree density, laser power, clearance distance, and moisture content affect the laser ablation process can help in optimizing the laser clearance operations for more efficient removal of tree obstacles in transmission lines.